Melatonin to Reduce Death Toll Due to COVID-19: From Innate to Adaptive Immune Response (Global Journal of Medical Research, 2020)
This paper highlights a new, nonspecific medication, which could be used both as a preventive and a curative measure to slow down the progression of Coronavirus disease 2019 (COVID-19) until a more specific treatment is available. The suggested treatment (immunomodulation) consists in the administration of melatonin, a substance shown to inhibit the innate (blind and usually harmful) immune response while facilitating the adaptive one, the only capable of fighting efficiently against the infection. In low oral doses, melatonin can be administered preventively to persons at risk and those already infected but still asymptomatic. High, intravenously administered doses may help critical patients under imminent threat of death. The combined use of both strategies will hopefully unblock the current overcharge of intensive care units by reducing new admissions and favoring healed patient discharge.
Keywords: melatonin; coronavirus; SARS-CoV-2; COVID-19 prevention; COVID-19 treatment